2019
DOI: 10.3389/fphys.2019.01261
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Force Microscopy Is a Potent Technique to Study Eosinophil Activation

Abstract: Eosinophils are multifunctional cells with several functions both in healthy individuals, and those with several diseases. Increased number and morphological changes in eosinophils have been correlated with the severity of an acute asthma exacerbation. We measured eosinophils obtained from healthy controls and individuals with acute asthma using atomic force microscopy (AFM). In the control samples, cells showed more rounded morphologies with some spreading, while activated cells from symptomatic individuals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Importantly, these eosinophils were fixed directly after venous blood sampling. In a similar study in which healthy and acute asthma donors' eosinophils were allowed to spread on glass at 37 • C (where eosinophils likely activate by adhesion) a marked difference was observed in their spreading and morphology when measured by AFM [209]. Although this conclusion was based on very few samples, this approach highlights the need to study cells in a functional setting.…”
Section: Eosinophil Basophils Granulocytes and Mast Cellsmentioning
confidence: 86%
“…Importantly, these eosinophils were fixed directly after venous blood sampling. In a similar study in which healthy and acute asthma donors' eosinophils were allowed to spread on glass at 37 • C (where eosinophils likely activate by adhesion) a marked difference was observed in their spreading and morphology when measured by AFM [209]. Although this conclusion was based on very few samples, this approach highlights the need to study cells in a functional setting.…”
Section: Eosinophil Basophils Granulocytes and Mast Cellsmentioning
confidence: 86%
“…Scale bars are 5 µm. Adapted from Eaton et al ([ 156 ], fig. 1 d,e , g,h ); copyright 2019, Frontiers in Physiology; .…”
Section: High-resolution Imaging Of Respiratory Modelsmentioning
confidence: 99%
“…In situ functional assessment of a variety of human muscle fibres [ 169 ] found that AFM measurements could reliably distinguish biopsies from both Duchene muscular dystrophy and Becker muscular dystrophy patients when compared with matched healthy individuals [ 169 ]. AFM has been employed to investigate morphological features of cells [ 170 ], where it can be used to evaluate morphological differences between asthmatic and healthy individuals [ 156 ]. In symptomatic asthmatic whole blood samples, it was shown that many highly activated eosinophils were present, with AFM identifying irregular spreading with multiple pseudopods when compared with the healthy samples, which appeared more round with less spreading [ 156 ] ( figure 4 c ).…”
Section: High-resolution Imaging Of Respiratory Modelsmentioning
confidence: 99%
See 1 more Smart Citation